Transliteration of Penang street food - Chee, Zia Mun (2015)
Translation is a process of transferring a written text from source language (SL) to target language (TL). Being a unique way of translation, transliteration refers to the method of translating a foreign word into a native language by preserving its pronunciation in the original language, also known as translation-by-sound. Unlike other translation methods, transliteration focuses more on pronunciation than meaning. The aim of this article is to identify the transliteration method used for translating street food from Chinese or Malay into English. Street food is ready-to-eat food or drink sold in a street or other public place, that located outdoor or under a roof which is easily accessible from the street such as at the market or fair, by a hawker or vendor, often from a portable food booth, food cart or food truck. Street foods reflect traditional local cultures and exist in an inexhaustible variety. This study will be carried out in Penang due to the fact that Penang is renowned for being chosen as one of the greatest street food cities. The data will include both the original name in Chinese or Malay and the translated name of street food in English. The data is categorised into few groups according to the types of food before analysed further to identify the translation method and the choice of Chinese character in transliteration. The result confirmed that many names of street food are translated to English using transliteration method. Other translation methods especially word-by-word translation and also loan word from Malay, English or other Chinese dialects are found widely used as well.